The effect of interpreters on eliciting information, cues to deceit and rapport - Ewens, Sarah (Legal and criminological psychology, 2016)
Background. The present experiment examined how the presence of an interpreter during investigative interviews affects eliciting information, cues to deceit and rapport. Method. A total of 60 native English speakers were interviewed in English and 183 non-native English speakers were interviewed in English (a foreign language) or through an interpreter who interpreted their answers sentence by sentence (short consecutive interpretation) or summarized their answers (long consecutive interpretation). Interviewees discussed the job they had (truth tellers) or pretended to have (liars). Results. Interviewees who spoke through an interpreter provided less detail than interviewees who spoke in their first language and a foreign language (English) without an interpreter. Additionally, cues to deceit occurred more frequently when interviewees spoke without an interpreter. The presence of an interpreter had no effect on rapport. Conclusion. The findings suggest that at present there are no benefits to using an interpreter with regard to eliciting information. Future research should investigate how best to utilize an interpreter to gain maximum detail from an interview.